Direct autotransfusion in the management of acute pericardial tamponade during catheter ablation for atrial fibrillation: An imperfect but practical method - Zhao, Xin; Liu, Jian-feng; Su, Xin; Long, De-yong; Sang, Cai-hua; Tang, Ri-bo; Yu, Rong-Hui; Liu, Nian; Jiang, Chen-xi; Li, Song-nan; Guo, Xue-yuan; Wang, Wei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Acute pericardial tamponade (APT) is one of the most serious complications of catheter ablation for atrial fibrillation (AF-CA). Direct autotransfusion (DAT) is a method of reinjecting pericardial blood directly into patients through vein access without a cell-salvage system. Data regarding DAT for APT are rare, and provide limited information. Our present study aims to further investigate the safety and feasibility of DAT in the management of APT during AF-CA procedure. Methods and results: We retrospectively reviewed 73 cases of APT in the perioperative period of of AF-CA from January 2014 to October 2021 at our institution, among whom 46 were treated with DAT. All included patients successfully received emergencypericardiocentesis through subxiphoid access guided by X-ray. Larger volumes of aspirated pericardial blood (658.4±545.2 ml VS. 521.2±464.9 ml), higher rates of bridging anticoagulation (67.4% VS. 37.0%) and surgical repair (6 VS.0) were observed in patients with DAT than without. Moreover, patients with DAT were less likely to complete AF-CA procedures (32/46 VS. 25/27) and had a lower incidence of APT first presented in the ward (delayed presentation) (8/46 VS. 9/27). There was no difference inmajor adverse events (death/ disseminated intravascular coagulation/ multiple organ dysfunction syndrome and clinical thrombosis) (0/0/1/0 VS. 1/0/0/0), other potential DAT-related complications (fever/ infection and deep venous thrombosis) (8/5/2 VS. 5/3/1), and length of hospital stay (11.4±11.6 d VS. 8.3±4.7 d) between two groups. Conclusion: DAT could be a feasible and safe method to deal with APT during AF-CA procedure.